Social infrastructure service delivery in South Africa: a bibliometric, visualization, and thematic analysis - Mashabela, Boy Johannes; Gumbo, Trynos; Ishola, Abdulrasaq Ajadi (Frontiers in Sustainable Cities, 2025)
IntroductionThis study conducted a bibliometric analysis of social infrastructure service delivery research in South Africa, using 69 Scopus-indexed journal articles published between 1994 and 2024.MethodsIn analysing the bibliometric data, Biblioshiny, VOSviewer, and Microsoft Excel were used to examine publication trends, prolific authors, and thematic developments in the field.ResultsThe first Scopus-indexed article appeared in 1999, with publication rates showing modest growth in the first decade (1999–2009), followed by a significant acceleration, increasing by over 200% between 2010 and 2019. Citation analysis revealed a consistent impact across publications, with notable peaks in 2010 and 2020. Leading contributors include Akinboade OA, Mokwena MP, and Maramura TC. Their studies focused on citizen satisfaction, service delivery protests, and public service reform. Key research themes encompassed water policy and infrastructure, citizen participation in service delivery, public service innovation, and informal settlement services. The study identified research gaps in public service inclusion for disadvantaged groups and citizen roles in infrastructure maintenance.DiscussionThe analysis demonstrates that while research in this field has grown since South Africa’s post-apartheid transition, certain critical areas remain underexplored. Despite being limited to Scopus-indexed articles, the study provides valuable insights into the evolution and current state of social infrastructure service delivery research in South Africa. The findings clarify the understanding of the literature landscape and establish a foundation for future research directions.